2014
DOI: 10.1016/j.carbon.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Filtration and inactivation of aerosolized bacteriophage MS2 by a CNT air filter fabricated using electro-aerodynamic deposition

Abstract: A B S T R A C TCarbon nanotubes (CNTs) were coated on a sample of glass fiber air filter medium at atmospheric pressure and room temperature using electro-aerodynamic deposition (EAD). In the EAD method, CNTs (diameter: 50 nm, length: 2-3 lm) were aerosolized, electrically charged, and injected through a nozzle. A voltage was applied externally between the ground nozzle and a planar electrode on which the sample was located. The charged CNTs were deposited on the sample in a vertically standing posture even at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…As demonstrated in Figure a, with increasing the embedded PET filament diameters, the removal efficiency and pressure drop of PA‐6 NF/N filters both exhibited a gradually decreased trend due to the increasingly fluffy packing structures supported by PET framework. This phenomenon could be explained very well with the classical theory that the cavity volume was inversely proportional to the pressure drop . Further analysis indicated that, the ripple‐like PA‐6 NF/N membrane embedded with 60 µm PET filament possessed a virtually unchanged removal efficiency of 98.74% and sharply decreased air resistance of 36.5 Pa in contrast to the flat and compact NF/N membrane (removal efficiency of 99.19% and air resistance of 52 Pa), indicating an essential improvement of filtration performance.…”
Section: Resultssupporting
confidence: 69%
“…As demonstrated in Figure a, with increasing the embedded PET filament diameters, the removal efficiency and pressure drop of PA‐6 NF/N filters both exhibited a gradually decreased trend due to the increasingly fluffy packing structures supported by PET framework. This phenomenon could be explained very well with the classical theory that the cavity volume was inversely proportional to the pressure drop . Further analysis indicated that, the ripple‐like PA‐6 NF/N membrane embedded with 60 µm PET filament possessed a virtually unchanged removal efficiency of 98.74% and sharply decreased air resistance of 36.5 Pa in contrast to the flat and compact NF/N membrane (removal efficiency of 99.19% and air resistance of 52 Pa), indicating an essential improvement of filtration performance.…”
Section: Resultssupporting
confidence: 69%
“…Due to their high specific surface area and adsorption capability CNTs have been increasingly used in environmental applications [4]. Recently, multi-walled and single-walled CNT filters were developed and found to be effective for multilog microbial removal from contaminated water by physical straining, puncture and depth filtration [5][6][7][8]. Furthermore, Gao et al [9] reported a mechanically stable, electrically conductive and flexible CNT-PVDF membrane and demonstrated that the filter can be effective and efficient for single pass nitrobenzene mineralization by sequential reduction-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the in situ growth strategy, the deposition method has also been widely used in manufacturing CNT‐based filters. Park and Hwang modified CNTs on glass‐fiber filters using electro‐aerodynamic deposition. In this method, the CNTs were aerosolized, electrically charged, and injected through a nozzle.…”
Section: Carbon‐based Purification Materialsmentioning
confidence: 99%